Atrionemertes greenlandica gen. et spec. nov. (Nemertini: Hoplonemertini) - Senz, W. (Zoologischer Anzeiger, 1993)
Atrionemertes greenlandica gen. et spec. nov. is described and illustrated. The species belongs to the monostiliferous hoplonemerteans. No oesophagus is developed and the foregut opens (together with the rhynchodaeum) into an atrium.